The Implementation of a Special Digital Program For Enhancing Students’ Character and Competencies at Muhammadiyah 5 Randublatung Junior High School - Siti Naviah Nurhayati; Widya Kusumaningsih; Joko Sulianto (Journal of Educational Sciences, 2026)
Digital transformation in education requires schools to adapt systematically to technological developments while ensuring character formation and competency enhancement. This study aims to analyze the implementation of a Special Digital Program in strengthening students’ character and competencies at Muhammadiyah 5 Randublatung Junior High School. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with the principal and teachers, and documentation analysis. Data analysis involved data reduction, data display, and conclusion drawing, with source triangulation to ensure validity. The findings reveal that the program was implemented through the integration of character values into technology-based learning and the reinforcement of digital literacy. The initiative fostered responsibility, discipline, and digital ethics, while improving 21st-century competencies such as critical thinking, creativity, collaboration, and problem-solving skills. The success of the program was supported by visionary leadership, teacher readiness, and an adaptive school culture. In conclusion, digital transformation should be positioned as an integrative strategy connecting pedagogical, cultural, and managerial dimensions to sustain educational quality.